Panoramic ultrasound imaging and MyotonPRO - Wegener, F.; Hoppe, M. W. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
This chapter focuses on the use of panoramic ultrasound imaging and the myotonometry-based digital palpation device MyotonPro for the diagnostics of Achilles and patellar tendons. Such new measurement methods and devices can be used to quantify parameters such as tendon length and stiffness practicable and reliable in sports and clinical settings. This enables the investigation of tendon-specific stresses induced by specific training loads and the characterization of related physiological or pathophysiological acute reactions and long-term adaptations of the tendon tissue. Regarding evidence-based prevention research, the importance of such new technologies is steadily increasing in order to identify possible risk factors of overuse sports injuries with a high burden such as tendinopathies.